A Meta-Analysis of Paraprofessional-Delivered Interventions to Address Challenging Behavior Among Students With Disabilities - Walker, Virginia L.; Carpenter, Megan E.; Lyon, Kristin J.; Button, Lindsey (Journal of positive behavior interventions, 2021)
Paraprofessionals report spending a substantial amount of time addressing challenging behavior in a range of school environments, yet identify behavioral intervention as a high-priority training area. The purpose of this meta-analysis was to systematically review and summarize single-case intervention studies involving paraprofessional-delivered behavioral interventions for students with disabilities. Descriptive findings suggest that, among the reviewed studies, paraprofessionals primarily provided behavioral support to students with autism spectrum disorder, intellectual disability, and multiple disabilities who engage in a wide range of challenging behaviors in both inclusive and noninclusive school environments. Overall, training largely was delivered by researchers and resulted in positive paraprofessional implementation outcomes. Likewise, paraprofessional-implemented behavioral interventions contributed to desirable changes in student challenging and appropriate behavior, with effect size estimates significantly higher for interventions delivered to early childhood–age students and within inclusive school settings. Implications for practice, limitations, and future research directions are described.